Classification of Defaulter in the Payment of Debt in Islamic Banking Practices from Sharī‘Ah Perspective - Hasan, Aznan; Haron, Muhamad Nasir; Mohamed, Mohd Faysal; Mana, Budeeman (International Islamic University Malaysia, 2021)
This paper discusses the issue of treatment of debt defaulter from Islamic perspective and its current practices in Islamic banking and finance. In brief, the paper begins with an overview of debt and its payment obligation. The paper also explains the current situation of treating defaulter in Islamic banking practices. The study also investigates and analyses various opinions and views of the classical and contemporary jurists in determining the types of defaulters and their treatment in the current practices. The paper concludes, among others, that besides the categorization of defaulters to solvent and insolvent, in modern Islamic banking practice, a new category namely, muta’atthir i.e able debtor who is facing temporary shortage of liquidity should also be introduced. These debtors are not insolvent if the ratio of their total assets and debts are considered. However, they are in situation of default due to temporary shortage of liquidity that they are facing. Hence, this new category will have its own ruling from Sharī‘ah point of view in terms of debt settlement and restructuring where it does not carry the ruling of insolvent debtor